The Income Tax Compliance Costs of Private Households: Empirical Evidence from Germany - Blaufus, Kay; Hechtner, Frank; Jarzembski, Janine K. (Public Finance Review, 2019)
Using a survey of more than 18,000 taxpayers in North Rhine-Westphalia (Germany), we estimate the income tax compliance costs of German households and study the determinants of these costs. We find that taxpayers need between 9.13 and 10.23 hours and spend €106 to meet their income tax obligations. The average total burden is between €228 (lower bound estimate) and €321 (upper bound estimate). The aggregate cost burden ranges between 2.03 percent and 2.92 percent of the German income tax revenues of tax year 2015. Although these costs have decreased significantly over recent years (mainly for self-preparers without self-employment income), international comparisons illustrate that the German burden is still located in the upper middle. The five most important cost drivers that increase individual costs are the use of tax advice, the appeal procedure, income, return complexity, and education. We cannot confirm that e-filing reduces taxpayers’ compliance costs.
CRIS-Team Scopus Importer:2020-08-10
Keywords: personal income tax; tax complexity; tax compliance costs; tax simplification